Prevalence of intestinal parasites in puppies marketed in Puno, Peru - Enríquez Añamuro, Carlos (2019)
The aim of this study was to determine the prevalence of intestinal parasites in puppies marketed in the city of Puno and to evaluate the possible association of the breed type and type of commercialization (formal, informal) with the presentation of intestinal parasitism. Faecal samples were taken from 172 puppies, without distinction of sex and breed type, between 1 and 4 months of age, from the informal market, as well as from veterinary centres and pet stores (formal). Samples were processed by direct examination and the flotation concentration technique with 33% zinc sulphate solution (GE 1.18). Of the 172 samples, 90 showed one or more eggs, cysts or oocysts of parasites, representing a prevalence of 52.3%. The prevalence of intestinal parasites in purebred and mestizo puppies were 44.2 and 60.5%, respectively, and of puppies from informal and formal trade were 66.3 and 38.4% respectively. The species found were Dipylidium caninum, Ancylostoma caninum, Toxascaris leonina, Toxocara canis, Trichuris spp, Giardia spp, Isospora spp and Sarcocystis spp. There were 11 cases of bi-parasitism, one of triparasitism and one of tetra-parasitism. The type of commercialization was associated with the presence of intestinal parasitism (p<0.05), but not with the breed.